2016
DOI: 10.1111/1440-1630.12353
|View full text |Cite
|
Sign up to set email alerts
|

Older peoples’ perspectives on time spent alone

Abstract: Enabling older people to balance time spent alone by addressing barriers to participation in the community in addition to finding engaging occupations to occupy time has the potential to prevent boredom, loneliness and improve wellbeing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…Despite the significant impact of loneliness on older adults, the difficulty in identifying this problem remains an obstacle for healthcare professionals to take measures [27,28]. In relation to this, different studies have tried to find out the role of loneliness in both institutionalised and community-dwelling older adults [7,[29][30][31][32][33][34], comprehend healthcare professionals' experience on older adults' isolation [28] and evaluate strategies to reduce loneliness in older adults [35,36]. However, more research focusing on understanding healthcare professionals' perceptions of the phenomenon of loneliness in older adults is needed [28,37,38] since evidence suggests that healthcare professionals receive insufficient training to address this important issue [37,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the significant impact of loneliness on older adults, the difficulty in identifying this problem remains an obstacle for healthcare professionals to take measures [27,28]. In relation to this, different studies have tried to find out the role of loneliness in both institutionalised and community-dwelling older adults [7,[29][30][31][32][33][34], comprehend healthcare professionals' experience on older adults' isolation [28] and evaluate strategies to reduce loneliness in older adults [35,36]. However, more research focusing on understanding healthcare professionals' perceptions of the phenomenon of loneliness in older adults is needed [28,37,38] since evidence suggests that healthcare professionals receive insufficient training to address this important issue [37,39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Studies included in this review were published between 2007 and 2019 and the age of participants ranged from 10-92 years. Two studies were child specific (Poulsen et al, 2007(Poulsen et al, , 2008, two related to young adults (Roy et al, 2009;Orsmond et al, 2013), four specified older people (Pritchard et al, 2015;Arthanat et al, 2016;Taylor et al, 2016a;Stanley et al 2017), four included participants up to middle age (Ashby et al, 2012;Siemon et al, 2013;Blanche et al, 2015;Goods and Millsteed, 2016) and the remaining studies included adults over 18 including older people (Natturlund, 2010;Packer et al, 2012;Makdisi et al, 2013;Taylor et al, 2016b;Hand et al, 2017;Hanne et al, 2018;Boland et al, 2019;Barclay et al, 2019). Ten studies noted a predominance of male participants; nine a predominance of female participants and one did not specify participant gender.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A number of studies further illustrate that ageing is associated with increased loneliness and social isolation. For example, Stanley et al (2017) found that more time spent alone was associated with increased loneliness and reduced physical and mental health for older people. Whilst Hand et al (2017) present multiple dimensions of social isolation for older adults who reported diminished social networks, due to reduced health and limited access to transport, and a desire for more social interaction and engagement.…”
Section: Agementioning
confidence: 99%
See 1 more Smart Citation
“…Attributes are 'those characteristics of a concept which appear over and over again' when the concept is defined [15]. Literature review indicated ten key attributes for the concept of loneliness in older adults: 'subjective phenomenon' [16][17][18][19][20][21], 'lack of meaningful interpersonal relationships' [16,[19][20][21][22][23][24][25], 'a wall of sorrow and pain loneliness' [16,[19][20][21][26][27][28], 'struggle for energy and resilience' [16,19,24,29,30], 'loneliness as a time-related experience' [16,24,31], 'lack and deprivation' [32][33][34][35], 'feeling useless, isolated and unable to keep up with the flow of life' [18, 20-23, 27, 28, 36].…”
Section: Attributes Of Loneliness In Older Adultsmentioning
confidence: 99%